Pengaruh Kompetensi Auditor, Etika Profesi Akuntan dan Peran Skeptisme Profesional Terhadap Kualitas Audit di KAP Wilayah Bali dan Jawa - Made Konny Koswara; Nyoman Sri Padmini; Happy Herawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to prove empirically: (1) the effect of auditor competence on audit quality, (2) the effect of the accounting profession on audit quality and (3) the effect of the role of skepticism on audit quality at KAP Bali and Java Region. The population used in this study were auditors who worked at KAP Bali and Java Region (not branches) totaling 372 auditors. The sampling technique in this study used purposive sampling method with a sample size of 258 auditors consisting of junior auditors, senior auditors and partners. The data analysis technique used is descriptive analysis and structural equation model (SEM-PLS). The results of this study indicate that the measurement of auditor competency variables, the accounting professional ethics and the role of professional skepticism have a positive effect on audit quality.